Percutaneous Radiofrequency Ablation Combined With Transarterial Chemoembolization Plus Sorafenib for Large Hepatocellular Carcinoma Invading the Portal Venous System: A Prospective Randomized Study - Ding, Xiaoyan; Sun, Wei; Chen, Jinglong; Li, Wei; Shen, Yanjun; Guo, Xiaodi; Teng, Ying; Liu, Xiaomin; Sun, Shasha; Wei, Jianying; Li, Wendong; Chen, Hui; et al. (Frontiers in Oncology, 2020)
Hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) portends a worse prognosis. The objective of this study was to compare the efficacy of percutaneous radiofrequency ablation (RFA) combined with transarterial chemoembolization (TACE) plus sorafenib to that of the the most commonly utilized regimen of TACE plus sorafenib in large HCCs with type I/II PVTT. An open-label, single-center, prospective, randomized trial of participants with tumors ≥5 cm and type I/II PVTT was performed. Participants with previously untreated HCCs were divided into two groups: RFA + cTACE + sorafenib (study group, n = 40) and cTACE + sorafenib (control group, n = 40). The primary endpoint was the objective response rate (ORR), the secondary endpoints included the overall survival (OS); time to progression (TTP); and toxicity. Prognostic factors were analyzed using cox-regression analysis. 80 patients were enrolled into this study with integrated clinical data. Under a median follow-up of 506 days, the median age was 57.5y (range: 28-80y). The ORR of study group was higher than control group (70% vs 22.5%, p<0.001). Furthermore, the median OS of study group was superior to that of control group (468 days vs 219 days, HR: 0.44 [95% CI: 0.25–0.78], P=0.005). The rates of adverse events in both groups were 100% (p>0.99). There were no treatment-related deaths. Base on a multivariate analysis for entire group, tumor encapsulation and an objective response were identified as the independent predictors of favorable OS. Treating large hepatocellular carcinomas with type I/II portal vein tumor thrombosis using RFA combined with TACE plus sorafenib was safe, well-tolerated, and had better efficacy than transarterial chemoembolization plus sorafenib alone.